On Shore VS on Board. Market segmentation of Cruise passengers Visiting Iceland and Marketing of Local Products and Services to Them - Charnykh, Iryna, 1987- (2015)
Tourism industry in Iceland has been growing incredibly fast during the past years. Cruise industry growth rate too has been very high, as Iceland continues gaining popularity as a cruise destination. Nevertheless, though certain amount of research has been made in this sphere, it doesn’t cover all of the important issues. This research is intended to examine one of them. The main goal of the research is to study cruise passengers coming to Iceland through their segmentation and to learn about marketing practices directed to them. Qualitative research method was used in the research. Personal interviews were chosen as means of collecting information in order to gain better insight of the participants’ perspective. The researcher took interviews with 10 people from different companies who interact with cruise passengers on regular basis at their working place. The researcher aimed to get an understanding about how these people experience differences between cruise passengers. It was also intended to learn which ways of marketing tourist products and services are considered the best by interviewees. The main findings reveal that participants feel the strongest difference between cruise passengers of different nationalities, passengers coming on different ships (size and type), and passengers coming during different time of the year. What concerns marketing towards cruise passengers, it’s almost exclusively carried out through the Internet. A good website, search engine optimization and word-of-mouth being participants’ most preferred methods. Value of these findings lies in gathering knowledge about who actually the customers are, how they differ, what they expect, and how it is better to reach them. Answering these questions makes it easier to deliver superior value to them. Á Íslandi hefur ferðaiðnaðurinn stækkað mjög mikið undanfarin ár. Komur skemmtiferðaskipa hafa jafnframt aukist mjög mikið, þar sem Ísland verður æ vinsælli áfangastaður farþega skemmtiferðaskipa. Þrátt fyrir að nokkrar rannsóknir hafi ...